Possibilities of Internet technologies in self-guided work of future engineers in learning a foreign language (Pedagogy of Higher and Secondary Education, 2014)
Gerasymchuk T. V. Possibilities of Internet technologies in self-guided work of future engineers in learning a foreign language.This paper deals with the problems of the usage of Internet technology and organization of future engineers’ self-guided work, which encourages disclosure of their internal reserves and promotes professional foreign language competence and positive social and psychological personality traits. The term of interactivity is understood as a way of self-merit of competency of future engineers with the help of information technologies.
Keywords: internet technology; interactivity; website; self-guided work of future engineers; the formation of professional foreign language competence; person’s positive social and psychological characteristics